Basic structure of a web page for psychological support to adolescents whose parents have cancer - Hellmüller, Jacqueline; Blasco Blasco, Tomás (Psicooncología, 2019)
When a father or a mother gets diagnosed with cancer, children are affected too. Adolescents are the most vulnerable group to suffer the consequences. They consider that their surrounding do not listen to their necessities. That is why we propose an innovative approach to create the elements of a psychological support website for adolescents with parental cancer. The procedure was based on conducting semistructured interviews with adolescents, affected parents and psycho-oncologist. Results been given from the comparison between the interviews that have been done in this research and the results of the scientific literature. We concluded that the website should include three fundamental elements: Information, coping strategies counseling, and the possibility to interact with other adolescents in the same situation as well as with professionals. It is of great importance to avoid that the website should be iatrogenic. That is the reason why we propose a filter’s system that allows to direct the adolescent to the adequate content for his/her situation. These filters avoid, as much as possible, the wrong misinterpretation and expectations that can generate confusion and discomfort.
Keywords: parental cancer; adolescents; online support; psychosocial functioning